PROGRAM BANTUAN BERAS MISKIN (RASKIN) DI DESA BANGKO MAKMUR KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Miftah Khurohmi Khurohmi; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research objective is to determine the distribution of Raskin and to evaluate the response of poor families who get help Rakin. The sample of 59 respondents were in subdistrict village Bangko Makmur District Bangko Pusako Rokan Hilir. Data was analyzed using descriptive method whit quantitative approach. That data collection is done by observastion, questionnaires, interviews, guided by the guidelinis for the interview. The results showed that the distribution of Raskin in Bangko Makmur villege goes well and smoothly because the majority of respondents 67,79% said good. This means that the distribution of Rakin Raskin and distribution in rural sub district Bangko Pusako Rokan Hilir already well underway. Raskin recipient community respondents attitudes in Bangko Pusako Rokan Hilir district very well, the majoritas of respondents 100,00% benefit from Raskin program organized by the government every year.Keywords: aid program, the distribution of Raskin